FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KECEMASAN IBU BERSALIN KALA 1 DI KLINIK EKA SRIWAHYUNI MEDAN DENAI TAHUN 2019 - Veronika, Anita; Br Sitepu, Aprilita; Natalia, Inri (STIKes Santa Elisabeth Medan, 2020)
Introduction: The psychological problem felt by the mother during labor is anxiety. Anxiety is a feeling disorder characterized by feelings of fear and deep concern. Pregnant women who experience labor anxiety have a high risk of labor complications, namely preeclampsia and prolonged labor. This study aims to determine the factors influencing the anxiety level of 1st time maternity at Eka Sriwahyuni Clinic Medan Denai 2019 Method: This type of research is analytic descriptive correlation study with a cross sectional approach. The populations are all 1st time maternity mothers who come to Eka Sriwahyuni Clinic in March-May 2019. The sample size is 21 respondents who are determined using the accidental sampling method. This study uses primary data and then processed with IBM SPSS Statistics 20 for Windows computer programs and presented in the form of an open tableResult: Based on the results of the analysis, Of the 21 respondents, the majority of respondents have moderate anxiety levels.Discussion: only the knowledge variable could prove a significant relationship with the level of anxiety of the first childbearing mother labor.